On Sumudu Transform Method in Discrete Fractional Calculus - Fahd Jarad; Kenan Taş (Abstract and Applied Analysis)
In this paper, starting from the definition of the Sumudu transform on a general time scale, we define the generalized discrete Sumudu transform and present some of its basic properties. We obtain the discrete Sumudu transform of Taylor monomials, fractional sums, and fractional differences. We apply this transform to solve some fractional difference initial value problems.